Psychosocial connections between drug addiction and suicidal tendencies in mothers and pregnant women - Helena Záškodná; Blanka Žižková (Psychology and its Contexts, 2010)
The study presents the interim results of research carried out on drug-dependent pregnant women and mothers. The aim of the study is to identify individual and social characteristics which, in combination, enable individuals to cope with life stress. The authors highlight several important risks and protective factors which are effective across multiple influence domains. Negative effects revealed by the study include dysfunctional key interpersonal relationships, unstable partnerships and family environment, housing problems and emotional disorders.